PENGEMBANGAN APLIKASI PENGOLAHAN DATA BARANG BUKTI DI POLRES BOYOLALI BERBASIS WEB - Pakarti, Moch. Bagoes; Budyastomo, Avin Wimar; Al Haris, Firdhaus Hari Saputro (Gaung Informatika, 2014)
Sat Tahti (Force of Detainees and Evidence) at Polres Boyolali which has the task to manage the evidence in this case a vehicle, provide information about the vehicle seized and prepare for the service to society. Sat Tahti has provided a media that can provide information to the public but tht application is difficult to operate and there is no provided media of communication between the user. So it is necessary to develop the ease of operation and the addition of the communication media between the community and police.The methods used for data collection is observation, interview, and literature. Analysis of the data used is DAD (Data Flow Diagram). The Development method is waterfall. Assessment is the method of five view.Final results can be explained as follows: (1) Simplify Sat Tahti manage data evidence the vehicle. (2) Provide ease of data retrieval based on the vehicle license plate number of the vehicle. (3) With the development of these applications can improve the communication between the community and police through the medium of communication provided.